Severance Pay and the Shadow of the Law: Evidence for West Germany - Laszlo Goerke; Markus Pannenberg (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
Due to the complexity of employment protection legislation (EPL) in Germany, there is notable uncertainty about the outcomes of dismissal conflicts. In this study we focus on severance pay and inquire whether its incidence and level varies in a systematic manner with the legal rules as defined by labour as well as tax law. We start with a theoretical model that generates the main observable outcomes of dismissal conflicts as potential equilibrium situations. Using German panel data (GSOEP), we put our theoretical model to an empirical test. Our main result is that the shadow of the law matters. Criteria regarding the validity of dismissals either found in respective legislation or defined by labour courts significantly affect the incidence and magnitude of severance pay. Moreover, restrictive changes in the taxation of severance pay have a negative causal impact on its incidence.
Keywords: J65; K31; C24; H24; C23; 330; severance pay; labour law; taxation; sample selection; survey data; Abfindung; Kündigungsschutz; Steuerrechtsprechung; Spieltheorie; Schätzung; Theorie; Deutschland